Lavender Essential Oil as Treatment for Chronic Migraine: A Protocol for Non-Inferiority Randomized Controlled Trial - Wang, Xiaocong (International Journal of Public Health and Medical Research, 2026)
This study is a randomized, investigator-blinded, controlled phase III clinical trial designed to compare the efficacy of daily atomized inhalation of lavender essential oil versus 50 mg sumatriptan tablets among Australians aged 18–65 years with chronic migraine, with a 3-month follow-up period. The primary outcome is the monthly reduction in headache days, defined as an improvement from moderate or severe pain to mild or no pain. Eligible participants diagnosed with chronic migraine by general practitioners and providing informed consent are randomized 1:1 to the intervention group (lavender essential oil) or the control group (sumatriptan tablets). This protocol aims to evaluate whether lavender essential oil is non-inferior to standard pharmaceutical treatment for chronic migraine management.